ORGANIZATIONAL BEHAVIOR OF EMPLOYEES OF THE YOUNGEST GENERATIONS: CHALLENGES FOR MANAGERS - BLAGA, Nataliia; HONCHAR, Danylo (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The current stage of enterprise development is characterized by profound socio-economic transformations driven by digitalization processes, globalization, and changes in forms of employment. In the context of the growing role of human capital as a key factor of organizational competitiveness, the issue of effective management of organizational behavior becomes particularly relevant. Significant changes in the workforce structure, associated with the active entry of the youngest generations into the labor market, create new challenges for management systems and human resource management. Military events in Ukraine have a substantial impact on the psychological state of employees, which is reflected in behavioral reactions, levels of engagement, communication processes, and the effectiveness of teamwork, thereby intensifying the need to adapt managerial approaches to contemporary conditions of enterprise functioning.The article is devoted to the analysis of the characteristics of organizational behavior of representatives of Generations Z and Alpha, who are currently shaping a new labor reality and significantly transforming approaches to human resource management. The key behavioral traits, motivational factors, values, and communication preferences of these generations, which distinguish them from previous cohorts of employees, are examined. The article outlines practical recommendations for building effective interaction with Generations Z and Alpha, contributing to increased engagement, productivity, and loyalty in a transformational business environment. Managerial challenges related to the integration of young employees into modern organizational structures are analyzed. The feasibility of adapting traditional approaches to human resource management with regard to intergenerational differences is substantiated. Practical recommendations for managers aimed at improving the effectiveness of managing the organizational behavior of young employees are formulated. Thus, the results of the study allow for a deeper understanding of the organizational behavior of Generations Z and Alpha and can be used to enhance managerial decision-making in the field of human resource management in order to increase the effectiveness of intergenerational interaction in modern organizations.
Keywords: Generation Z; Generation Alpha; organizational behavior; young employees; managerial challenges; digital culture; leadership styles; organizational communication; HR strategies